FOSTERING SCIENTIFIC LITERACY THROUGH LOCAL CONTEXTS: THE EFFECTIVENESS OF CULTURALLY RESPONSIVE WORKSHEETS - Apriana Djara; Insih Wilujeng; Laifa Rahmawati (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
The integration of science literacy in the independent curriculum has not been optimally implemented and remains limited, failing to address contextual aspects relevant to everyday life. This study aims to enhance science literacy through a culturally responsive learning approach, supported by student worksheets. The development method employed was a mixed-methods approach, incorporating data collection through interviews, observations, and science literacy tests, utilizing a one-group pretest-posttest design. The results showed that there was an effect on improving students' science literacy with an N-Gain value of 0.52 which showed an increase in science literacy skills, and a paired sample T-Test value of 0.00 <0.05 which showed that there was an effect of the approach on science literacy and the effect size test showed a significant effect with a value of 1.99, so it can be concluded that the application of culturally responsive teaching-based student worksheets effectively improves science literacy on vibration and wave material for junior high school science subjects.